Molecular Characterization and Genotyping of Multi-drug Resistant Uropathogenic Escherichia coli - Reda, Ranim (2023)
Urinary tract infections (UTIs) are the most common cause of bacterial infections in outpatients worldwide. More than 90% of complicated and uncomplicated UTIs are caused by Uropathogenic E. coli (UPEC). While females are disproportionately affected, there remains a significant gap in the understanding of gender-based genotypic variations in E. coli causing urinary tract infections. Therefore, the aim of this study was to characterize 62 UPEC isolates recovered from male and female patients with urinary tract infections in Lebanon. Whole-genome sequencing (WSG) was used to study differences in the resistance profiles, virulence determinants, plasmid contents, and clonal relatedness. Antimicrobial phenotypic susceptibility tests against 22 antibiotics from nine different classes revealed significant antimicrobial resistance patterns, with 20% demonstrating carbapenem resistance, and 55% being extended-spectrum β-lactamase producers (ESBL). The in silico resistome profiles of the isolates revealed the presence of over 61 resistance determinants including blaCTX-M-15 (55%; n=34), blaCTX-M-27 (11%; n=8), blaTEM-1B (31%; n=19), blaOXA-1 (31%; n=19), blaNDM-5 (18%; n=11), and blaOXA-224 (5%; n=3). Common sequence types (STs) included high-risk clones, such as ST131, ST10, ST410, and ST167 with the isolates being distributed over 25 different STs, revealing clonal heterogeneity. Combined results from PCR-based replicon typing (PBRT) and PlasmidFinder showed that the most common Inc group were IncFIB and IncFIA. Gender-based differences in resistance patterns and phylogeny were observed. Isolates recovered from males were ESBL producers and commonly classified under virulent B2 phylogroup while from females were mainly carbapenem-resistant and belonged to phylogroups B2 and A. Our findings revealed gender-based differences among UPEC isolates and provided a better understanding of the underlying mechanisms of virulence and resistance.